2003
DOI: 10.1353/sof.2003.0051
|View full text |Cite
|
Sign up to set email alerts
|

Race and the Probability of Arrest

Abstract: Although blacks are arrested disproportionately for most types of violent crimes, disagreement persists as to the extent to which official arrest data are indicative of differential offending behavior or selection bias on the part of law enforcement personnel. Using data from the National Incident-Based Reporting System (NIBRS), we assess the effect of an offender's race on the probability of arrest for 335,619 incidentsofforcible rape, robbery, and assaultin 17 states during 1999. The baseline modelfor these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 29 publications
4
105
1
Order By: Relevance
“…Many social scientists have debated whether arrests in general are an accurate measure of unlawful behavior (for example, see Blumstein 1993;D'Alessio and Stolzenberg 2003;DeFleur 1975;Tonry 1995). Most researchers examining this question have concluded that race plays a comparatively small role in arrests for serious offenses, such as murder and robbery, but a significant role in the policing of more minor offenses.…”
Section: Data Sources and Research Designmentioning
confidence: 99%
“…Many social scientists have debated whether arrests in general are an accurate measure of unlawful behavior (for example, see Blumstein 1993;D'Alessio and Stolzenberg 2003;DeFleur 1975;Tonry 1995). Most researchers examining this question have concluded that race plays a comparatively small role in arrests for serious offenses, such as murder and robbery, but a significant role in the policing of more minor offenses.…”
Section: Data Sources and Research Designmentioning
confidence: 99%
“…Race differences in labeling events often are attributed to disparity in power between members of dominant and oppressed groups (Reiman 1998;Schur 1971). Yet, once differential involvement in crime is taken into account, differences in arrest, conviction and incarceration rates tend to diminish (Blumstein 1982;D'Alessio and Stolzenberg 2003).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It is plausible that the relationship of race and gender with the likelihood of arrest is due to one of several other confounding factors that were not measured and not included in the analyses. Previous research suggests that the demeanor of the suspect (Piliavin & Briar, 1964;Smith et al, 1984;Visher, 1983), the physical appearance of the suspect (Piliavin & Briar, 1964), victim characteristics such as race and age (D'Alessio & Stolzenberg, 2003;Smith et al, 1984), relationship between suspect and victim (D'Alessio & Stolzenberg, 2003), and victim request for arrest (Black & Reiss, 1970;Lundman et al, 1978;Smith et al, 1984;Visher, 1983) are also influential in the decision to arrest.…”
Section: Discussionmentioning
confidence: 99%